Dysregulated Expression of Glycolipids in Tumor Cells: From Negative Modulator of Anti-tumor Immunity to Promising Targets for Developing Therapeutic Agents - Daniotti, Jose Luis; Lardone, Ricardo D.; Vilcaes, Aldo A. (Frontiers in Oncology, 2016)
Glycolipids are complex molecules consisting of a ceramide lipid moiety linked to a glycan chain of variable length and structure. Among these are found the gangliosides, which are sialylated glycolipids ubiquitously distributed on the outer layer of vertebrate plasma membranes. Changes in the expression of certain species of gangliosides have been described to occur during cell proliferation, differentiation and ontogenesis. However, the aberrant and elevated expression of gangliosides has been also observed in different types of cancer cells, thereby promoting tumor survival. Moreover, gangliosides are actively released from the membrane of tumor cells, having a strong impact on impairing anti-tumor immunity. Beyond the undesirable effects of gangliosides in cancer cells, a substantial number of cancer immunotherapies have been developed in recent years that have used gangliosides as the main target. This has resulted in successful immune cell- or antibody-responses against glycolipids, with promising results having been obtained in clinical trials. In this review, we provide a general overview on the metabolism of glycolipids, both in normal and tumor cells, as well as examining glycolipid-mediated immune modulation and the main successes achieved in immunotherapies using gangliosides as molecular targets.